Dr. Charles L. Suffel: Scholar, teacher, mentor, friend. Issue 4 (16th April 2022) - Gross, Daniel; Kahl, Nathan; Luttrell, Kristi; Saccoman, John T.
Abstract: Dr. Charles L. Suffel (1941–2021) was an influential mathematics educator and scholar at Stevens Institute of Technology for more than half a century. The Managing Editor of Networks for 20 years, Suffel's reach extended far beyond the Stevens campus. He coauthored dozens of graph theory papers and mentored more than a dozen Ph.D. thesis students. In this article, we discuss his contributions to the field of network reliability theory and his legacy as a teacher and mentor.